Body composition of rheumatoid arthritis patients and their perceptions and practices regarding diet, nutritional supplements and other treatments - Lombard, Louise Ann (Stellenbosch : Stellenbosch University, 2011)
Thesis (MNutr)--Stellenbosch University, 2011